Pengaruh model project based learning terhadap kemampuan berpikir kreatif peserta didik pada pembelajaran IPAS kelas V sekolah dasar - Lina Indriani; Senny Widia Oktari; May Syarah (Didaktika Dwija Indria, 2025)
This research aims to determine the significant influence of using the Project Based Learning model on students' creative thinking abilities in science and science learning for class V elementary schools, as well as to identify significant differences in creative thinking abilities between students who take part in Project Based Learning and those who take expository learning. This research is a quasi-experimental type with a nonequivalent comparison group design. The instrument used in the study was a creative thinking ability test. Data analysis was carried out through prerequisite tests and hypothesis testing. Prerequisite tests include normality and homogeneity tests, while hypothesis testing is conducted using paired sample t-tests and independent sample t-tests. The research results show that the use of the Project Based Learning model has a significant effect on students' creative thinking abilities, and there are significant differences between students who follow this model and those who take expository learning.